Lung Stereotactic Body Radiotherapy (SBRT) Using Spot-Scanning Proton Arc (SPArc) Therapy: A Feasibility Study - Liu, Gang; Zhao, Lewei; Qin, An; Grills, Inga; Deraniyagala, Rohan; Stevens, Craig; Zhang, Sheng; Yan, Di; Li, Xiaoqiang; Ding, Xuanfeng (Frontiers in Oncology, 2021)
Purpose We developed a 4D interplay effect model to quantitatively evaluate breathing-induced interplay effects and assess the feasibility of utilizing spot-scanning proton arc (SPArc) therapy for hypo-fractionated lung stereotactic body radiotherapy (SBRT). The model was then validated by retrospective application to clinical cases. Materials and Methods A digital lung 4DCT phantoms was used to mimic targets in diameter of 3cm with breathing motion amplitudes: 5, 10, 15, and 20 mm, respectively. Two planning groups based on robust optimization were generated: (1) Two-field Intensity Modulated Proton Therapy (IMPT) plans and (2) SPArc plans via a partial arc. 5,000 cGy relative biological effectiveness (RBE) was prescribed to the internal target volume (ITV) in five fractions. To quantitatively assess the breathing induced interplay effect, the 4D dynamic dose was calculated by synchronizing the breathing pattern with the simulated proton machine delivery sequence, including IMPT, Volumetric repainting (IMPTvolumetric), iso-layered repainting (IMPTlayer) and SPArc. Ten lung patients’ 4DCT previously treated with VMAT SBRT, were used to validate the digital lung tumor model. Normal tissue complicated probability (NTCP) of chestwall toxicity was calculated. Result Target dose were degraded as the tumor motion amplitude increased. The 4D interplay effect phantom model indicated that motion mitigation effectiveness using SPArc was about five times of IMPTvolumetric or IMPTlayer using maximum MU/spot as 0.5 MU at 20 mm motion amplitude. The retrospective study showed that SPArc has an advantage in normal tissue sparing. The probability of chestwall’s toxicity were significantly improved from 40.2 ± 29.0% (VMAT) (p = 0.01) and 16.3 ± 12.0% (IMPT) (p = 0.01) to 10.1 ± 5.4% (SPArc). SPArc could play a significant role in the interplay effect mitigation with breathing-induced motion more than 20 mm, where the target D99 of 4D dynamic dose for patient #10 was improved from 4,514 ± 138 cGy [RBE] (IMPT) vs. 4,755 ± 129 cGy [RBE] (SPArc) (p = 0.01). Conclusion SPArc effectively mitigated the interplay effect for proton lung SBRT compared to IMPT with repainting and was associated with normal tissue sparing. This technology may make delivery of proton SBRT more technically feasible and less complex with fewer concerns over underdosing the target compared to other proton therapy techniques.